MARRIAGE, SPIRITUALITY AND MODERN SOCIETY: Al-Ghazali’s Thought - Azizah, Uswah (Teosofia: Indonesian Journal of Islamic Mysticism, 2016)
Marriage ideally should be a meaningful relationship, but in reality it is not the same. Modern society is questioning marriage that make them confronts dilemma which weaken social responsibility and family ties which, then, susceptible to domestic violence and even ended by divorce. This dilemma lead modern society seek for happiness outside marriage by choosing alternative of marriage; cohabitation, gay-parent family, or staying single (celibacy). The problem is modern society fail to find the meaningful relationship inside marriage. They fulfill material needs but fail fulfilling spiritual needs. This study is qualitative research which uses literature approach by focusing on the study of al-Gazali’s thought about the virtue of marriage in tasawuf perspective. The data is analyzed using content analysis approach to reveal the content of al-Gazali’s books. The virtue of marriage is the ethical significant of what lies behind the order of marriage. The virtue of marriage is that it is one of abstinence (riyadah an-nafs), it is done when fasting and restraining sight cannot curb sexual desire anymore. It is a necessary virtue for the conduct of spiritual exercises leading to union with God. Another virtue of marriage is that it is an act of devotion (‘ibadah). It said so because there are many benefits (maslahah) inside marriage. Besides it can safeguard self from sinning if sight and adultery, it also beneficial in perpetuating mankind conform to the love of God. The virtue of marriage, in fact, can overcome the dilemma of modern society.